Finance act, 1965: annotated: income tax, capital gain tax & corporation tax provisions - Commerce Clearing House (New York : Commerce Clearing House, 1965)
An Act to grant certain duties, to alter other duties, and to amend the law relating to the National Debt and the Public Revenue, and to make further provision in connection with Finance. The act divides capital gains into two classes. Short-term and long term gains
"Advance copy."
II 17/01/2019
Loans
Keywords: Taxation